Effect of an arch-type tunnel in the foundation soil on the seismic response of dikes - Tan, Jian Ming (2017)
This report studies the dynamic response of the dikes due to earthquake loading when there is an arc-shaped tunnel in the foundation soil below it. The study is being carried out using the PLAXIS 2D software by comparing output such as the ground displacement, settlement and peak ground acceleration experienced by the soil model. The basis of comparison is through varying the sizes and the positioning of the tunnels, and applying the entire soil model to an input of earthquake acceleration data as the dynamic loading.